Scientific Aspects of Water Extract Katola (Arcangelisia flava L. Merr) as Antidiarrhea Agent in Mina South Sulawesi - Muhammad Akhram Larisu; Sudarsono .; Susi Iravati; Arief Nurrochmad (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2010)
Water extract of katola (Arcangelisia flava L. Merr) stem is traditionally used in communities Muna Distric for the treatment of many diseases, including anti diarrhea. According to the information of Muna Distric Health Office, diarrhea is one of the 10 groups diseases in this district. The objective of this study was conducted to determine the potential antimicrobial, acute toxicity and identified of the water extract of bioactive compounds and alkaloid relative concentration content. Infection of microbial was induced by oral administration of Shigella flexneri ATCC 12022 1 x 108 CFU/mL. Boiling water of katola dose 12 mg/kg, 24 mg/kg and 48 mg/kg body weight and the antibiotic ampicillin 24 mg/kg administered 2 times daily for 5 days. The number of S. flexneri in feces were determined every day. The toxicity of water extract of katola stem is determined based on the value of LD50 acute oral toxicity testing followed by guidelines OECD 423. The bioactive compounds was determined by bioautografi method and the concentration alkaloid relative content was calculated as berberine hydrochloride. The results showed that boling water extract of katola stem did not cause toxic symtoms, with LD50 > 31.5 g/kg body weight (unclassified) or 104 times the dose therapy of human. In vitro, the Minimum Inhibition Concentration (MIC) and Minimum Bactericidal Concentration (MBC)value of the boiling water were 1.2 and 2.4%, respectively. In vivo, the boiling water dose 48 mg/kg body weight given twice a day have an effect on eradication the S. flexneri 100% by day 5. Bioactive compounds of antimicrobial in the water extract is alkaloid berberine HCl. A cocentration of berberine hydrochloride in water exract stem and leaves dosage use of the public were 16.7% and 0.75% respectively.Key words: Katola, toxicity, anti diarrhea, antimicroba, Arcangelisia flava L. Merr